2019
DOI: 10.1111/bju.14948
|View full text |Cite
|
Sign up to set email alerts
|

Hemi‐ablative low‐dose‐rate prostate brachytherapy for unilateral localised prostate cancer

Abstract: Objectives To report clinical outcomes of the Hemi‐Ablative Prostate Brachytherapy (HAPpy) trial evaluating treatment‐related toxicity and effectiveness of hemi‐gland (HG) low‐dose‐rate (LDR) prostate brachytherapy as a focal approach to control unilateral localised prostate cancer. Patients and Methods Single institution phase IIS pilot study of patients treated with focal 4D Brachytherapy™ (BXTAccelyon, Burnham, Buckinghamshire, UK). The primary outcome was patient‐reported toxicity 24 months after implant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It has been reported that the treatmentrelated toxicities and biochemical outcomes of hemigland LDR brachytherapy for unilateral localized prostate cancer are broadly similar to those of whole-gland brachytherapy. Although, post-implant dose to the urethra and rectum was significantly lower in hemi-gland brachytherapy, compared with whole-gland brachytherapy [22]. It is difficult to conclude which focal LDR brachytherapy (hemi-gland vs. MRI-based target) is superior at this time.…”
Section: Table 3 Frequencies Of Genitourinary (Gu) and Gastrointestinal (Gi) Toxicitiesmentioning
confidence: 90%
“…It has been reported that the treatmentrelated toxicities and biochemical outcomes of hemigland LDR brachytherapy for unilateral localized prostate cancer are broadly similar to those of whole-gland brachytherapy. Although, post-implant dose to the urethra and rectum was significantly lower in hemi-gland brachytherapy, compared with whole-gland brachytherapy [22]. It is difficult to conclude which focal LDR brachytherapy (hemi-gland vs. MRI-based target) is superior at this time.…”
Section: Table 3 Frequencies Of Genitourinary (Gu) and Gastrointestinal (Gi) Toxicitiesmentioning
confidence: 90%
“…Most causes of dropout were not stated or simply described as "lost to follow-up". Reasons stated when reported included oncological unfavourable evolution (n=2) [14], PDE5 inhibitors use (n=11) [16,30], withdrawn consent (n=19) [11,14,21] and death due to unrelated causes [32].…”
Section: Acceptability Of Sexual Follow-upmentioning
confidence: 99%
“…A clinical pilot study by Langley and co-authors suggested that treatment-related toxicity and biochemical outcomes after hemi-gland implants were comparable with whole glands: sexual potency was preserved in 73% and 67% of hemi- and whole gland groups, respectively ( p = 0.84). Treatment relapses in both the groups were observed as 3% [ 21 ]. Cosset et al .…”
Section: Discussionmentioning
confidence: 99%
“…Only minimal acute toxicity was observed, but no data of long-term tox-icity was available [22]. Studies of Langley et al [21] and Cosset et al [22] used traditional prescription doses of 145 Gy. However, radiation doses equal to or above a BED of 200 Gy have demonstrated improved outcomes, Stone and others have published long-term data on biopsy results, which demonstrated that a biological equivalent dose (BED) of 220 Gy (using an α/β of 2) can result in a negative biopsy rate of 98.4% [23,24].…”
mentioning
confidence: 99%